2012
DOI: 10.1002/anie.201207017
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Intramolecular Coupling of the Terminal Borylene and a Carbonyl Ligand of [Cp(CO)2MnBtBu]

Abstract: Cyclic complex 2 with bridging carbonyl ligands was synthesized from a facile and reversible intermolecular carbonyl-borylene ligand coupling reaction at room temperature. Complex 2 exhibits an unprecedented coordination mode for boron-metal complexes, which is also reflected in its remarkable (11)B NMR chemical shift of -57.2 ppm. Findings from spectroscopic, X-ray, and computational studies are presented, along with a proposed mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 81 publications
2
25
0
3
Order By: Relevance
“…This complex reacts with 2 equiv of supermesityl isonitrile (Mes*NC, Mes* = 2,4,6-tritertbutylphenyl) to form complex 15, which features a bridging and a semibridging carbonyl between the boron atom and the metal center (Scheme 4). 105 The calculated 106 bridging (O)C2−B distance of 1.586 Å falls within the range expected for a B−C single bond. The (O)C2−Mn distance of 1.938 Å is significantly longer than a typical terminal (O)C−Mn distance (1.75−1.85 Å), which is consistent with the reduced bond order expected for the bridging coordination mode.…”
Section: Inorganic Chemistrysupporting
confidence: 66%
“…This complex reacts with 2 equiv of supermesityl isonitrile (Mes*NC, Mes* = 2,4,6-tritertbutylphenyl) to form complex 15, which features a bridging and a semibridging carbonyl between the boron atom and the metal center (Scheme 4). 105 The calculated 106 bridging (O)C2−B distance of 1.586 Å falls within the range expected for a B−C single bond. The (O)C2−Mn distance of 1.938 Å is significantly longer than a typical terminal (O)C−Mn distance (1.75−1.85 Å), which is consistent with the reduced bond order expected for the bridging coordination mode.…”
Section: Inorganic Chemistrysupporting
confidence: 66%
“…Thec alculated free energy of I1 is 12.1 kcal mol À1 ,w hich should be accessible at room temperature.T he coupling of the base-stabilized borylene ligand of I1 with one CO ligand forms I2,a nalogous to an umber of recently-isolated complexes containing side-on-bound basestabilized boraketenes (O = C = BRL) and boraketenimines (RN = C = BRL). [21] Unfortunately,a ttempts to locate at ransition state between I1 and I2 failed. As ystematic scan of the potential energy surface of the BÀC carbonyl bond cleavage in I2 showed that the energy increases in that direction (Supporting…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[4] Them echanism also hinges on the partial transfer of aC Ol igand from the metal to an arylborylene ligand, aphenomenon that also forms the basis of our recent work on borylene-CO coupling and the liberation of monovalent boron species from metal scaffolds,i ncluding our recent syntheses of boraketenes,boraketenimines,and aborylene dicarbonyl. [21]…”
Section: Communicationsmentioning
confidence: 99%
“…[17] A bulky diarylgermylene reported by Power and co-workers was shown to undergo H 2 addition as well as double CO insertion/ coupling into both aGe ÀCand an aryl-isopropyl bond of the ligand. [18] In the area of low-valent boron chemistry,adicoordinate cAAC-supported aminoborylene reported by Stephan, Bertrand, and co-workers was shown to add H 2 across the B À C cAAC bond and coordinate CO. [19] In the last few years,o ur research group has greatly expanded the reactivity scope of CO with low-valent boron compounds.T he use of first-row transition-metal borylene precursors led to several examples of base-triggered borylene-carbonyl coupling reactions, [20] the reductive coupling of ab orylene to two CO ligands at chromium, [21] as well as the complete cleavage of CO at an iron(0) bis(borylene) complex upon coordination of ac AACl igand. [22] Thea ddition of strong s-donor/p-acceptor ligands (cAAC, CO,RNC) to iron and manganese borylene carbonyl compounds provided facile routes to tricoordinate CO-stabilized metal-free borylenes.…”
mentioning
confidence: 99%